The (un)authorized preacher - Stange, Klaus Andreas (Vox Scripturae - Revista Teológica Internacional, 2015)
The present article approaches the theme of identity and of authority in the pastoral ministry. The author explores the text of 2 Co 3.4-4.18, highlighting two images used by the apostle Paul in this text that can be used as hermeneutical keys for the approaching of the theme. The two images make reference to the episode of Moses’ face that shines after his encounter with God in the Mount Sinai and to the account of creation, where the creation of the human being as “image and likeness” of God is affirmed. The theme of identity in the pastoral ministry will be developed from the vision that understands the “image and likeness” as a reflective image, not as a represented image. From this premise, some implications and consequences for the pastoral ministry are derived.